Impact of degradation and time of sampling on gut Microbiome composition in wild-caught marine fish - Yufei Zhou; Alejandro Trujillo-González; Simon Nicol; Marion Boutigny; Roger Huerlimann; Stephen D. Sarre; Dianne Gleeson (Scientific Reports)
Abstract The gut microbiome has the potential to be an effective indicator of individual and population health in fish given its sensitivity to internal and external stressors. However, without consistent and tested validated sampling protocols, the gut microbiome’s potential as a reliable indicator may be limited. Routine sampling of wild free-living fish caught by commercial fisheries rarely occurs at the time of capture and more commonly occurs hours, days, or weeks after fish capture when the catch is unloaded in port. This delay in sampling provides time for the degradation and decomposition of the microbiome community potentially compromising the reliability of gut microbiome analyses. Unfortunately, comprehensive and systematic analyses on post-capture changes in the gut microbiome communities of wild marine fish are lacking, limiting the reliability of microbiome studies. Here, we investigated the post-mortem changes in the gut microbiome of one wild-caught marine fish, skipjack tuna (Katsuwonus pelamis), at five different time points (immediately, 2 h, 24 h, 12 days, and 24 days after fish capture). The decomposition of the gut microbiome community occurred within the first 24 h if the samples were not preserved immediately. Over time, the relative abundance of Vibrionaceae decreased while Bradyrhizobiaceae increased, indicating the potential of these two families to serve as gut microbiome degradation indicators. Our findings highlight the importance of timely preservation in gut microbiome studies of wild-caught fish. Without appropriate preservation, both the diversity of the gut microbiome and the relative abundance of key microbial families change significantly within 24 h. To obtain reliable and representative results, we recommend preserving gut samples as soon as possible after capture, ideally within two hours, and no later than 24 h.s.